The confidante : the untold story of the woman who helped win WWII and shape modern America - Gorham, Christopher C. (Citadel Press, Kensington Publishing Corp., 2023)
The first-ever biography of Anna Marie Rosenberg, a Hungarian Jewish immigrant who became a real power behind national policies critical to America winning World War II and prospering afterwards, chronicles her extraordinary career as FDR's special envoy to Europe during the war and an adviser to five presidents.